2019
DOI: 10.1371/journal.pone.0213058
|View full text |Cite
|
Sign up to set email alerts
|

Maternal factors contributing to low birth weight deliveries in Tshwane District, South Africa

Abstract: Background Low birth weight continues to be a main cause of child morbidity and mortality. Low birth weight can cause complications in adult life, and is therefore a public health concern. In this study, we determined the maternal factors that contribute to low birth weight (LBW) deliveries in Tshwane District, South Africa. Methods We conducted a case control study of 1073 randomly selected mothers who delivered babies in four hospitals in the district. We reviewed ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
76
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 26 publications
12
76
2
6
Order By: Relevance
“…Taha and friends These studies reported teenage mothers have an increased risk of delivering LBW babies compared to older women (16,17,27). However, this nding was inconsistent with those found by (19) and (18) who reported older women have an increased risk of LBW as compared to younger women.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Taha and friends These studies reported teenage mothers have an increased risk of delivering LBW babies compared to older women (16,17,27). However, this nding was inconsistent with those found by (19) and (18) who reported older women have an increased risk of LBW as compared to younger women.…”
Section: Discussionmentioning
confidence: 90%
“…For instance some studies have reported that risk of delivering low birthweight babies among teenage mothers is higher than that of older women (16,17). However, other studies older mothers are more likely to experience these birth outcomes (18,19).…”
Section: Introductionmentioning
confidence: 89%
“…Similarly, the study in Ethiopia was carried out in an urban area where the economic level of women tend to be higher than those from the rural area and the impact of better economic status on the prevalence of low birthweight is already described [29,30]. In contrast, rate in excess were reported in South Africa (38.5%) in 2014 [31], and in a study conducted in Zimbabwe (16.7%) [32]. The reason behind this higher prevalence in the South African and Zimbabwean studies could be related to the higher prevalence of human immuno-de ciency virus (HIV) infection [33].…”
Section: Discussionmentioning
confidence: 99%
“…Last, post-strati cation weights were adjusted to the age-sex-race distribution produced by Statistics South Africa based on population estimates. Analyses were based on a dataset with imputation values generated by the NIDS data team (18). All analyses were conducted using Stata 15 (Stata Corporation, College Station, TX).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Variables associated with stunting and severe stunting were combined in a nal multiple logistic regression model. (17,18).…”
Section: Sample Characteristicsmentioning
confidence: 99%